The Use of Wordwall Application for Speaking Skills at The XI Grade MA Ibnu Ali - Luluatul Mubasyiroh; Siti Maria Ulfa (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Wordwall is a digital learning platform that allows teachers to create interactive activities such as quizzes, games, and speaking prompts to enhance student participation. This research aims to explore the use of the Wordwall application in teaching English speaking skills, since speaking skills are the ability to communicate thoughts and ideas in a clear, structured, and meaningful way. This includes keeping the audience engaged, organizing ideas logically, using correct pronunciation and appropriate intonation, and analyzing both teachers’ and students’ perceptions of its effectiveness in improving fluency and proficiency. This qualitative study was conducted at MA Ibnu Ali, specifically involving XI grade students in a private Islamic senior high school in Lepelle Village, Sampang, Indonesia. Data were collected through classroom observation and semi-structured interviews with English teachers and students. The findings show that Wordwall can promote student motivation, increase classroom interaction, and provide a more enjoyable learning experience. It also helps reduce students’ speaking anxiety and encourages active involvement. However, some obstacles remain, such as limited vocabulary and student restlessness. This research implies that digital tools like Wordwall can support more student-centered and interactive language learning. Teachers are encouraged to integrate such platforms to foster creativity, critical thinking, and improved speaking performance in EFL classrooms.